Rekomendasi Praktis untuk Rekonsiliasi - Andreas Maurenis Putra (Reformed Center for Religion and Society, 2018)
ABSTRACT: Today, humans are always faced with the complexity of the acute world situation. This situation is nothing but an increasingly worsening environmental crisis. This emergency situation is inseparable from the increasingly exalted anthropocentric ego. The assumption that eliminates intrinsic value to other ecosystems and the wrong way of life leads to the separation of relations between humans and the surrounding reality.The interdependent context between all ecosystems is degraded due to the wrong attitude of life from humans. The loss of the relationship brought a variety of environmental damage which caused the destruction of human existence itself. Poverty, hunger, war, global warming, floods and drought are a few of the critical phenomena of nature. For these increasingly emergency natural phenomena, this thesis is written as a critical reflection for humans to re-examine their nature as religious, social and ecological creatures as well as concrete action that must be done to reconstruct relations (reconciliation) with nature, with the surrounding environment and especially reconciliation with his own life through ecological metanoia and a new lifestyle.Â KEYWORDS: relation, antrophosentrism ego, ecological exigent, multidimensional perspective, awareness, reconciliation, repentance and new lifestyle.